Savanna Life – evaluating board game players’ revealed preferences to inform conservation and development planning in the Greater Serengeti-Mara Ecosystem - Nielsen, Martin Reinhardt; Borgerhoff Mulder, Monique; Skjærvø, Gine Roll; Klöckner, Christian A.; Moe, Espen; Meilby, Henrik; Hartsteen, Hans Peter; Graae, Bente Jessen (Frontiers in Conservation Science, 2025)
IntroductionConservation and development planning is complex and can involve trade-offs and conflicts of interest. Games are an increasingly popular approach to exploring such conflicts and facilitating discussion and future planning. However, few studies have compared the preferences of different stakeholders in such games.MethodsThe board game Savanna Life was played in 12 communities (24 games with 96 players, resulting in 2,889 observations) in 2018 and 2019 within the Greater Serengeti-Mara Ecosystem, characterised by sharp conservation-agropastoral livelihood trade-offs. The game was designed to capture the challenges experienced by communities and provide a safe space for exploring alternative livelihood and investment strategies. We explore how players of different genders, ethnicities, and nationalities maximise their payoffs within the game's logic, allocate preferences across the conservation-development nexus, and change preferences under growing constraints during the game.ResultsUsing revealed preferences for game moves as an indicator, we found that, particularly men, prioritised maximising individual benefits over the game’s primary objective of winning collectively. We also found that players generally preferred moves representing agro-pastoral production over moves aligned with Western development objectives. Moves with negative conservation implications were least preferred. Players also clearly adapted their preferences to increasing constraints. Preferences varied among players based on gender, ethnicity, and nationality, with development and conservation planning implications.DiscussionPost-game follow-up revealed that players considered the game realistic, and they stated planning real-life changes to how they make livelihood decisions based on insights gained while playing the game, suggesting that the game can motivate behavioural change through cognitive transfer. These results support the usefulness of games, such as Savanna Life, in providing insights for a sustainable future. However, the main benefit may be facilitating community debates after the research team departs.